Answer:
2.69827 × 10⁹
Step-by-step explanation:
any questions?
Answer:
x = -6/5
y =7/5
Step-by-step explanation:
2x + y = - 1
x - 2y = - 4
Multiply the first equation by 2 so we can eliminate y
2(2x + y = - 1)
4x + 2y = -2
Add this to the second equation
4x + 2y = -2
x - 2y = - 4
---------------------
5x + 0y = -6
Divide by 5
5x/5 = -6/5
x = -6/5
Multiply the second equation by -2 so we can eliminate x
-2(x - 2y = - 4)
-2x+4y = 8
Add this to the first equation
2x + y = - 1
-2x+4y = 8
---------------------
0x + 5y = 7
Divide by 5
5y/5 = 7/5
y =7/5
The total value is:
5. 5 x 10 ^5 * 23 x 10^3 =
= $126.5 * 10^8 =
= $1.265 x 10^10
Answer: B )
Answer:
C
Step-by-step explanation:
divide 22.5 by 10
=2.5
so
f=2 1/2c
1) 4/(1/5)
=4 ÷ 1/5
to divide fractions, multiply by the reciprocal/inverse of 1/5
=4 * 5/1
=20
4) (7/9)/7
=7/9 ÷ 7
to divide fractions, multiply by the reciprocal/inverse of 7
=7/9 * 1/7
multiply numerators; multiply denominators
=(7*1)/(9*7)
=7/63
simplify by 7
=1/9
7) (9/10)/6
= 9/10 ÷ 6
to divide fractions, multiply by the reciprocal/inverse of 6
= 9/10 * 1/6
multiply numerators; multiply denominators
= (9*1)/(10*6)
= 9/60
simplify by 3
= 3/20
ANSWER: 1) 20; 4) 1/9; 7) 3/20
Hope this helps! :)